ALMA observations of a metal-rich damped Ly α absorber at z = 2.5832: evidence for strong galactic winds in a galaxy group. Issue 2 (11th June 2018) - Fynbo, J P U; Heintz, K E; Neeleman, M; Christensen, L; Dessauges-Zavadsky, M; Kanekar, N; Møller, P; Prochaska, J X; Rhodin, N H P; Zwaan, M
ABSTRACT: We report on the results of a search for CO(3–2) emission from the galaxy counterpart of a high-metallicity Damped Ly α Absorber (DLA) at z = 2.5832 towards the quasar Q0918+1636. We do not detect CO emission from the previously identified DLA galaxy counterpart. The limit we infer on M gas / M ⋆ is in the low end of the range found for DLA galaxies, but is still consistent with what is found for other star-forming galaxies at similar redshifts. Instead we detect CO(3–2) emission from another intensely star-forming galaxy at an impact parameter of 117 kpc from the line of sight to the quasar and 131 km s −1 redshifted relative to the velocity centroid of the DLA in the quasar spectrum. In the velocity profile of the low- and high-ionization absorption lines of the DLA there is an absorption component consistent with the redshift of this CO-emitting galaxy. It is plausible that this component is physically associated with a strong outflow in the plane of the sky from the CO-emitting galaxy. If true, this would be further evidence, in addition to what is already known from studies of Lyman-break galaxies, that galactic outflows can be traced beyond 100 kpc from star-forming galaxies. The case of this z = 2.583 structure is an illustration of this in a group environment.